The choice of remanufacturing strategy for the OEM with third-party remanufacturers' advantages. (February 2023) - Fang, Chang; Fan, Shuyi; Qiu, Yiwen
Highlights: The roles of cost and quality advantage in third-party remanufacturers are highlighted. In-house remanufacturing is not always in an inferior position. Both repairing cost and customers' perception of returned quality are essential for the OEM's optimal remanufacturing strategy. Outsourcing with the obvious quality advantage is dominant in remanufacturing. High environmental impact or low acceptance of the remanufactured product causes a conflict between profit and environment. Abstract: Outsourcing remanufacturing is a commonly adopted business practice under which original equipment manufacturers (OEMs) outsource remanufacturing to third-party remanufacturers (TPRs) and focus on new products. Motivated by different advantages from TPRs, we develop two models to characterize the features: (1) the TPR has a cost advantage by improving remanufacturing system and device (Model C); (2) the TPR has a quality advantage from brand guarantee (Model Q). The results suggest that in-house remanufacturing seems to be in an inferior position, but actually it is better than outsourcing if TPRs' advantages and the customers' perception of returned quality are unobvious. Both repairing cost and customers' perception of returned quality are essential for the OEM's optimal remanufacturing strategy. The outsourcing is dominant in the relatively high repairing cost or customers' perception of returned quality. Moreover, the obvious quality advantage plays the dominant role in outsourcing. Furthermore, we analyze the environmental impact and consumer surplus of remanufacturing strategies and identify the condition under which strategy benefits the environment and customers. When the environmental impact (acceptance) of the remanufactured product is relatively high (low), the optimal strategy presents a conflict between environment and customers' benefit.